(untitled) (GAIMS Journal of Medical Sciences, 2022)
Sternal foramen is a common developmental anomaly of the sternum, resulting from impaired fusion of the two mesenchymal halves. Though most cases are harmless and only detected incidentally, proximity to heart and lungs may lead to hazardous complications like pneumothorax or cardiac tamponade during acupuncture or sternal puncture procedures. Sound anatomical knowledge of the sternum and pre-procedural screening may help minimize the risk of these complications.